AB0170 Ccr9+ pathogenic thelper cells from primary sjÖgren's syndrome patients are characterised by deregulated pathways associated with effector t cell function. (12th June 2018) - Blokland, S.; Wichers, C.G.; Pandit, A.; Kruize, A.A.; Radstake, T.R.; van Roon, J.A.
Abstract : Background: CCR9 +Th cells produce large amounts of IFN-γ and IL-10, lack CXCR5 expression but have features similar to Tfh cells and the recently described pathogenic PD1 +CXCR5 cells, including expression of ICOS, PD-1, IL-21 and Bcl6, but no CXCR5 expression. CCR9 Th cells and their ligand CCL25 are elevated in salivary glands of primary Sjögren's syndrome (pSS) patients. Since CCR9 Th cells strongly induce antibody production and robustly respond to IL-7, which is indicated to play an essential role in pSS pathogenesis and in formation of ectopic lymphoid structures, these cells may play an important role in pSS immunopathology. Objectives: The goal of this study was to identify the molecular dysregulation of CCR9 Th cells in pSS patients. Methods: CCR9+, CXCR5 +and CCR9-CXCR5- Th cells were sorted from peripheral blood of 7 healthy individuals and 7 pSS patients and RNA sequencing of these sorted cell subsets was performed. Computational analysis identified differentially expressed genes (DEG) and gene expression networks. Pathway enrichment analysis was performed in order to assess differentially regulated pathways. Target genes are technically validated and knockdown experiments will assess the functional role of identified targets. Results: The sorted Th subsets could robustly be distinguished based on their transcriptomes. In the CCR9 +Th cell subset 2777 DEGs (1249 up and 1528 down) were identified between healthy controls and pSS patients, and 1416 and 1077 in the CXCR5 +and CCR9-CXCR5- subsets, respectively. Using network analysis 15 modules were constructed, consisting of genes showing coherent expression patterns. Four modules of interest were selected based on pathway enrichment analysis, revealing pathways involved in e.g. cytokine and chemokine production, proliferation and migration. DEGs of interest within these networks were selected, including upregulated expression of integrin αE, integrin α1 and downregulation of regulatory T cell associated genes FoxP3 and IL2RA. Expression of these markers is being validated using flow cytometry. In addition, knockdown of predicted key transcription factors is studied to reveal their role in the pathogenic potential of CCR9 +Th cells. Conclusions: Transcriptomic analysis of CCR9 +Th cells from pSS patients revealed multiple dysregulated pathways previously shown to be involved in increased effector T cell function. Upregulation of genes associated with pathogenicity and downregulation of regulatory T cell associated genes were found in pSS patients. Targeting predicted key molecules might reveal (novel) therapeutic targets to halt pathogenic processes induced by CCR9 +Th cells. Disclosure of Interest: None declared